ActivEpi Companion Textbook A supplement for use with the ActivEpi CD-ROM - Kleinbaum, David G.; Sullivan, Kevin M.; Barker, Nancy D.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This Companion Textbook supplements the ActivEpi CD-ROM, sold separately. The ActivEpi CD-ROM provides a multimedia presentation of concepts, commonly taught in an introductory epidemiology course. ActivEpi mixes a full array of media to motivate, explain, visualize and apply epidemiological concepts. Virtually all of the material on the ActivEpi CD-ROM is included in the Companion Textbook. Because individuals differ in their learning skills, the ActivEpi CD-ROM and the ActivEpi Companion Textbook offer readers different but related options on how to learn epidemiology. The Textbook can be used as a hardcopy reference of the textual materials contained on the CD-ROM, as a resource for the practice exercises, as a general reference, or even a self-contained textbook. The ActivEpi CD-ROM uses: Video to instill real-world motivation for learning and applying epidemiological concepts Narrated Expositions to teach the concepts using high-quality audio synchronized with text, pictures, and animations Quizzes to provide self-evaluation of basic terms and concepts Data Desk to provide practice applying the methods learned to real data Navigational Tools such as a dynamic table of contents, index and glossary, to allow easy-to-use methods for working through content Web Links to augment the material on the CD with complementary content authored by others. ActivEpi includes 15 lessons and over 50 hours of content via more than 250 launchable activities and homework exercises. It can be used in a variety of teaching formats: distance learning, self-paced learning, on-campus courses, and short courses. For the latest additions to ActivEpi, visit David Kleinbaum's website. http://www.sph.emory.edu/~dkleinb/activepi.htm
Introduction -- Objectives and Methods of Epidemiologic Research -- Validity of Epidemiologic Research -- Epidemiologic Analysis -- Glossary -- Index.
Keywords: Statistics; Epidemiology; Statistics; Statistics for Life Sciences, Medicine, Health Sciences; Epidemiology